2021
DOI: 10.2196/22745
|View full text |Cite
|
Sign up to set email alerts
|

Shared Decision-Making With a Virtual Patient in Medical Education: Mixed Methods Evaluation Study

Abstract: Background Shared decision-making (SDM) is a process in which clinicians and patients work together to select tests, treatments, management, or support packages based on clinical evidence and the patient’s informed preferences. Similar to any skill, SDM requires practice to improve. Virtual patients (VPs) are simulations that allow one to practice a variety of clinical skills, including communication. VPs can be used to help professionals and students practice communication skills required to engag… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…Specifically, our results showed that the recall score for medical history for the VP testing was two-thirds of the score for USP testing, while the corresponding VP score for physical examination was more than twice that of the USP score. These findings indicate that multiple choices might provide more hints, allowing PHC providers to guess a correct action more easily [ 14 , 26 ]. Although searching for keywords for consultation or actions leads to less bias than the hints provided by multiple choices, this interface might decrease the usability of VPs, particularly when the interaction does not provide enough options or fuzzy searches.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, our results showed that the recall score for medical history for the VP testing was two-thirds of the score for USP testing, while the corresponding VP score for physical examination was more than twice that of the USP score. These findings indicate that multiple choices might provide more hints, allowing PHC providers to guess a correct action more easily [ 14 , 26 ]. Although searching for keywords for consultation or actions leads to less bias than the hints provided by multiple choices, this interface might decrease the usability of VPs, particularly when the interaction does not provide enough options or fuzzy searches.…”
Section: Discussionmentioning
confidence: 99%
“…There is some evidence that VP user interfaces and usability may influence VP-based assessment outcomes [ 14 , 25 ]. The extent to which a VP may serve as a quality assessment tool needs further research [ 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…One of the tools could be defined as partially autonomous because a trained instructor had had to perform some of the functions (Ochs et al, 2019). Regarding the patient type employed for the training, the vast majority of the tools had used virtual patients (n = 19; 79.17%) with the appearance of a real person (Ali et al, 2020;Bánszki et al, 2018;Borja-Hart et al, 2019;Chae et al, 2023;Deladisma et al, 2008;Du et al, 2022;Guetterman et al, 2019;Hwang et al, 2022;Jacklin et al, 2021;Kleinsmith et al, 2015;Maicher, Kellen R. et al, 2019;Ochs et al, 2019;Perez et al, 2022;Plass et al, 2022;Real, Francis J., MD et al, 2017;Rouleau et al, 2022;Sapkaroski et al, 2022;Sezer & Sezer, 2019;Shorey et al, 2020). Of these, 94.74% (n = 18/19) had responded with a voice (n = 18/24; 75%), except for the tool published by (Du et al, 2022).…”
Section: Features Of the Virtual Toolsmentioning
confidence: 99%
“…A second objective was to involve patients in the design of a virtual patient simulation and inform the design process. (Jacklin et al, 2021) United Kingdom…”
Section: Englishmentioning
confidence: 99%
“…Through the collaboration, the researchers noted the need to improve the delivery of feedback to students as part of the training. The tool was effective in changing medical students' attitudes regarding the value of patient focus and shared decision-making (Jacklin et al, 2021). Foster et al (2016) showed the importance of feedback on students' empathic responses in interactions with VPs.…”
Section: Introductionmentioning
confidence: 99%